Trauma responsive organisations : the trauma ecology model - Mahon, Daryl (Emerald points., 2022)
Practitioners, organisations and policy makers in health and social care settings are increasingly recognising the need for trauma-informed approaches in organisational settings, with morbidity and financial burdens being of growing concern. Servant leadership has a unique focus on emotional healing, service to others as the first priority, in addition to the growth, well-being and personal and professional development of key stakeholders. Mahon provides a 'how to' approach to the systematic implementation of the Trauma Ecology Model for those working in both trauma specific, and non-specific organisations. He goes beyond the idea of trauma-informed care principles only, and seeks to incorporate trauma responsiveness at all levels, including leadership, supervision, treatment, through an implementation framework. Unique to this approach is the focus on servant leadership, the first of its kind. Servant leadership is used as the foundation to operationalize several of the six principles of trauma-informed care, making organizations a safer and healthier environment for employees and service users.